Da institucionalização à adoção: escuta ativa de crianças em situação de acolhimento - ROCHA, Isabela Silva (2018)
Listening to children is a matter of great importance, especially in the context of institutional reception and preparation for the adoption process. Therefore, the purpose of this work was to understand the transition from institutionalization to adoption from the perspective of the child itself and the listening of children from the perspective of the professionals of the host institutions. Two empirical studies, descriptive, cross-sectional, qualitative approach were carried out, using the methodology of the collective case study. Study 1 aimed to identify feelings and expectations that institutionalized children, already deprived of family power and with the ongoing adoption process, attribute to the transition from institutionalization to adoption. Five children participated in this study, once that the field of research has exhausted. The data collection began with a consultation to the Individual Plan of Attendance, a report that made it possible to know about the participants life history. Afterwards, two meetings were held, the first one was a playful session and the second was made use of the Thematic Story-Design procedure, with four specific themes: Draw what a child likes to do in the host institution until adopted; Draw a child who is waiting for adoption; Draw what you think a child who is living in the institution feels, away from the family of origin; Draw how would be a family you would like to have. The obtained data from the Play Session and Theme-Story Design were analyzed and interpreted according to the method of free inspection of the material from the comprehension process, sustained in the winnicottian psychoanalysis. The importance of active listening with institutionalized children, who are waiting for adoption, was highlighted as a way to enable them to express their feelings and anxieties and to enable them to make a better transition to the surrogate family. The second study aimed to understand the work of professionals from a host institution, especially regarding the performance of listening to children. Thus, ten professionals responded to an open interview, mediated by the presentation of a figure that was accompanied by the following request: "Looking at this figure, talk about what it is like to work in a host institution and listen to what children are trying to tell you ". A semistructured interview was also conducted, with the purpose of accessing sociodemographic data, information about the routine and other aspects related to the work of the participants, emphasizing the listening of the children by them. The data were analyzed in a descriptive-interpretative manner, consonant with the method of Psychoanalytic Narratives. The results gave visibility to the need for public policies aimed at the continuous training, recognition and valorization of professionals so that they can more effectively serve the best interests of children who are institutionalized so that they are free of possible prejudices, having been assured and respected their civil, social and cultural rights.